Risk factors for major amputation in hospitalised diabetic foot patients. (19th October 2015) - Namgoong, Sik; Jung, Suyoung; Han, Seung‐Kyu; Jeong, Seong‐Ho; Dhong, Eun‐Sang; Kim, Woo‐Kyung
Abstract: Diabetic foot ulcers are the main cause of non‐traumatic lower extremity amputation. The objective of this study was to evaluate the risk factors for major amputation in diabetic foot patients. Eight hundred and sixty diabetic patients were admitted to the diabetic wound centre of the Korea University Guro Hospital for foot ulcers between January 2010 and December 2013. Among them, 837 patients were successfully monitored until complete healing. Ulcers in 809 patients (96·7%) healed without major amputation and those in 28 patients (3·3%) healed with major amputation. Data of 88 potential risk factors including demographics, ulcer condition, vascularity, bioburden, neurology and serology were collected from patients in the two groups and compared. Among the 88 potential risk factors, statistically significant differences between the two groups were observed in 26 risk factors. In the univariate analysis, which was carried out for these 26 risk factors, statistically significant differences were observed in 22 risk factors. In a stepwise multiple logistic analysis, six of the 22 risk factors remained statistically significant. Multivariate‐adjusted odds ratios were 11·673 for ulcers penetrating into the bone, 8·683 for dialysis, 6·740 for gastrointestinal (GI) disorders, 6·158 for hind foot ulcers, 0·641 for haemoglobin levels and 1·007 for fasting blood sugar levels. The risk factors for major amputation in diabetic foot patients were bony invasions, dialysis, GI disorders, hind foot locations, low levels of haemoglobin and elevated fasting blood sugar levels.